Re-revision knee arthroplasty in a tertiary center: infection and multiple previous surgeries were associated with poor early clinical and functional outcomes - Fritsch-Seerhausen, Lennart Ulrich Burkhard von; Sabah, Shiraz A.; Xu, Joshua; Price, Andrew J.; Merle, Christian; Alvand, Abtin (The journal of arthroplasty, 2023)
Background - The incidence of re-revision knee arthroplasty (re-revision KA) is increasing and associated with high complication and failure rates. The aim of this study was to investigate re-revision rates, complications, and patient-reported outcomes following re-revision KA and factors associated with poor outcome. - Methods - This was a retrospective cohort study of 206 patients (250 knees) undergoing re-revision KA at a major revision center from 2015 to 2018. The mean follow-up was 26 months (range, 0 to 61) and mean age at re-revision KA was 69 years (range, 31 to 91 years). The main indications for surgery were prosthetic joint infection (PJI) (n = 171/250, 68.4%) and aseptic loosening (n = 25/250, 10.0%). We compared re-revision rates, joint function, and complications for aseptic and infective indications. Logistic regressions were performed to identify risk factors for further reoperation. - Results - The estimated re-revision rates at 2 years were 28.7% (95% confidence interval [CI]: 22.7-35.9) and at 4 years were 42.0% (95% CI: 32.8-52.6). Mean Oxford Knee Score was 26 points (range, 1 to 48). Mean EuroQoL-5D-5L utility was 0.539 (range, -0.511 to 1.000). Multivariable analyses demonstrated that PJI (Odds Ratio [OR] 2.39, 95% CI 1.06-5.40, P = .036), greater number of previous surgeries (OR 1.18, 95% CI 1.04-1.33, P = .008), and higher Elixhauser score (OR 1.06, 95% CI 1.01-1.13, P = .045) were independently associated to further surgery. - Conclusion - Re-revision KA carried a high risk of early failure. Multiple revised joints and patients with more comorbidities had worse function. Patients undergoing re-revision KA for PJI should be counseled to expect higher failure rates and complications than patients who have aseptic indications.
Online verfügbar 27 January 2023, Version des Artikels 7 June 2023
Gesehen am 21.09.2023